Qwater: aplicativo para suporte às análises físico-químicas de água para irrigação - Medeiros, Arlan de (Universidade Federal Rural do Semi-Árido, 2018)
In the semi-arid region, due to the scarcity of good quality water, many farmers use saline water for crop irrigation. Under high salinity conditions, crop growth, leaf surface expansion and the primary carbon metabolism of many plants are negatively affected due to salinity effects. For this reason, salinity has been considered one of the most important water factors for irrigation. In this paper, an application that can aid in the interpretation of water analysis reports was developed, as this was already a expressed demand by teachers and other professionals related to the project code PEB00003-2017 registered in PROPPG entitled "Sistema Inteligente de Monitoramento do Uso Eficiente da Água e do Risco de Salinização dos Solos no Polo de Desenvolvimento Integrado Assu/Mossoró".
Monografia
Keywords: Salinidade; Irrigação; Aplicativo; Salinity; Irrigation; Application; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO